(untitled) (GEON Journal (Management, Organizations and Business), 2015)
This article is the analysis of information collected from the observatory trade with merchants of the city of Manizales. We intend to show a pattern of trade industry as an important economic activity that contributes to the GDP of the city and contributing to the social and economic development of the people; identifying characteristics of Manizales (intermediate city) with a market where a range of strategies that are based on trends and conditions that give their companies competitiveness applies. Conceptually overview of trade competitiveness, sales strategies to be competitive, promotional strategies, competitiveness in commerce and trade strategies used by traders are addressed. It is that the Manizales traders use a variety of tactics and promotional and customer service which are in tune with direct marketing and relationship marketing, which are aimed at maintaining captivated customers, showing that planning is needed to succeed and be competitive in developing their businesses, demonstrating their ability and creativity to meet the target audience. In like manner they are aimed at meeting the planned corporate objectives in order to achieve dynamic increase its share in the market and of course, face competition and overcome the economic crisis which has hit both the business.